MicroRNAs/LncRNAs Modulate MDSCs in Tumor Microenvironment - Liu, Xiaocui; Zhao, Shang; Sui, Hongshu; Liu, Hui; Yao, Minhua; Su, Yanping; Qu, Peng (Frontiers in Oncology, 2022)
Myeloid-derived suppressor cells (MDSCs) are a heterogeneous group of immature cells derived from bone marrow that play critical immunosuppressive functions in the tumor microenvironment (TME), promoting cancer progression. According to base length, Non-coding RNAs (ncRNAs) are mainly divided into: microRNAs (miRNAs), lncRNAs, snRNAs and CircRNAs. Both miRNA and lncRNA are transcribed by RNA polymerase II, and they play an important role in gene expression under both physiological and pathological conditions. The increasing data have shown that MiRNAs/LncRNAs regulate MDSCs within TME, becoming one of potential breakthrough points at the investigation and treatment of cancer. Therefore, we summarize how miRNAs/lncRNAs mediate the differentiation, expansion and immunosuppressive function of tumor MDSCs in TME. We will then focus on the regulatory mechanisms of exosomal MicroRNAs/LncRNAs on tumor MDSCs. Finally, we will discuss how the interaction of miRNAs/lncRNAs modulates tumor MDSCs.